Utilization Pattern of Bamboo in North Eastern Region of India (Indian Journal of Extension Education, 2022)
The study was conducted in the states of Assam and Meghalaya of India in the year 2020- 21. Total 380 respondents were selected using multistage sampling method. The states Assam and Meghalaya, were selected purposively based on availability of processing units and highest productivity, respectively among the North Eastern states. The utilization pattern was classified into household, construction, handicraft, agricultural purpose, and food and other uses. The results indicated of total of 42062 numbers of bamboo culms were utilized by sample respondents. The construction uses contributed highest number of culms and accounted of 35541 numbers (84.50%), followed by household uses 4001 culms (9.51%) and agricultural uses 1350 culms (3.21%). The food consumption was observed of 2.11 per cent while for making handicraft products use was only 0.62 per cent of the total uses. The least bamboo was utilized in the musical instruments (0.05%). The use of bamboo would remain a vital part of the livelihood of people of the region. Therefore, with advancement of technology, trainings and support from government schemes on bamboo in the region would provide ample scope to develop new products and marketing opportunities and thereby generating employment and income to the youth.